2019
DOI: 10.1021/jacs.9b09352
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Coordination Environment in Single-Atom Catalysts to Achieve Highly Efficient Oxygen Reduction Reactions

Abstract: Designing atomically dispersed metal catalysts for oxygen reduction reaction (ORR) is a promising approach to achieve efficient energy conversion. Herein, we develop a template-assisted method to synthesize a series of single metal atoms anchored on porous N,S-codoped carbon (NSC) matrix as highly efficient ORR catalysts to investigate the correlation between the structure and their catalytic performance. The structure analysis indicates that an identical synthesis method results in distinguished structural di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
486
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 802 publications
(505 citation statements)
references
References 47 publications
15
486
0
4
Order By: Relevance
“…Figure 3b shows typical current profiles for methanol oxidation reaction in neutral-pH media. These curves reflect that the methanol oxidation onset potentials are 1.03 and 1.37 V (vs. RHE) for Ir-NSG and Ir/C, respectively, indicating a higher adsorption energy of OH* on Ir-NSG, which could be derived from a larger intermolecular hardness factor of the bond between Ir shell site and OH induced by the lower electronegativity of S ligand 35,44 . The higher OH* binding energy is supposed to correlate with binding energies of other oxygen intermediates (e.g., O* and OOH*) and hence OER activities.…”
Section: Synthesis and Structural Characterization Of Ir-nsg Catalystmentioning
confidence: 80%
“…Figure 3b shows typical current profiles for methanol oxidation reaction in neutral-pH media. These curves reflect that the methanol oxidation onset potentials are 1.03 and 1.37 V (vs. RHE) for Ir-NSG and Ir/C, respectively, indicating a higher adsorption energy of OH* on Ir-NSG, which could be derived from a larger intermolecular hardness factor of the bond between Ir shell site and OH induced by the lower electronegativity of S ligand 35,44 . The higher OH* binding energy is supposed to correlate with binding energies of other oxygen intermediates (e.g., O* and OOH*) and hence OER activities.…”
Section: Synthesis and Structural Characterization Of Ir-nsg Catalystmentioning
confidence: 80%
“…For the sake of evaluating the practical application of our catalyst, the durability and methanol‐tolerance are key parameters . As is known to all, 20 % Pt/C catalyst is easily poisoned by methanol . As a comparison, the methanol‐tolerance of the Co−CoO X /Co−N−C and Pt/C catalysts were noted at −0.3 V vs. SCE.…”
Section: Resultsmentioning
confidence: 99%
“…No general rule has been found to control the relative position of metal atom and heteroatoms at the active site. It has been reported that different kinds of metal ions have different tendencies when interacting with heteroatoms in precursors [59] . For example, Co 2+ and Ni 2+ can coordinate with N and S elements at the same time, while Fe 3+ only interacts with N, resulting in products of FeN 4 S 2 , CoN 3 S 1 and NiN 3 S 1 , respectively.…”
Section: Discussionmentioning
confidence: 99%